Analisis Produktivitas Tenaga Kerja Sektor Industri Besar Dan Sedang Daerah Kabupaten Dan Kota Provinsi Jawa Timur 2015-2019 - Rahmat Dwi Zakaria (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study was to analyze the Labor Productivity of the Large and Medium Industrial Sector in the Regencies and Cities of East Java Province. The data used is secondary data obtained from the Central Bureau of Statistics of the Regency and City of East Java Province in 2017-2019. The analytical method used in this research is panel data regression. The results of this study indicate that the Regency and City Minimum Wages, the average length of schooling have a significant positive effect on the Labor Productivity of the Large and Medium Industrial Sector, while the Human Development Index has a significant negative effect on the Labor Productivity of the Large and Medium Industrial Sector. East Java.